ANALYSIS OF FISH SPECIES BIODIVERSITYANDABUNDANCE OF GANGAM DAM, GWARAM, JIGAWA STATE, NIGERIA - Alkasim, A.; Jauro, I. A.; Muhammad, A. M.; Modu, A. B. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The fish diversity and abundance of Gangama dam were studied for the period of twelve months from July 2018 to June 2019. The study investigated 16 species of fish belonging to 10 families which showed that Cichlidae was the most abundant and dominant family with ( 5605; 76.07%) consisting of four species of Hemichromis bimaculatus (1942; 26.36%, a dominant), Oreochromi saureus (1813; 24,61%), Sarotherodon melanotheron (1073; 14.57%) and Sarotherodon galilaeus (776; 10.53%) while monthly abundance revealed Oreochromis aureus (793; 43.74%) in January 2019, The family Arapaimidae was the least abundant represented by only one (1) specie (Heterotis niloticus (4; 0.05%). Using Shannon-Weiner index of general diversity (H), monthly species diversity between months were 0.78; 0.74;0.79; 0.82; 0.87; 0.60; 0.706; 0.42; 0.52; 0.67; 0.68; 0.66. Relative abundance (RA) calculated had a total number of 7366 fish and Simpson's index of dominance (D) showed that Gangama dam was shared by all species since the result was 0.1and monthly index of dominance range were 0.17; 0.21; 0.21; 0.16; 0.15; 0.26; 0.27; 0.44; 0.64; 0.24; 0.22 and 0.20.The research recommended that frequent restocking measure and avoidance of over fishing should be considered to prevent species extinction